Perancangan Standar Operasional Prosedur (SOP) Penagihan Piutang sebagai Solusi Mengurangi Risiko Keterlambatan Pembayaran - Ardellia, Azahra Sazida; Raharso, Sri; Sutisna, Ma’mun; Chaniago, Harmon; M, Mukaram (Yayasan Daarul Huda Kruengmane, 2024)
Optimal management of trade receivables is crucial for maintaining a company's financial stability, especially for companies that implement a credit sales policy. While providing flexibility to partners, this policy also increases the risk of delayed payments or uncollectible receivables. This article discusses the development of a Standard Operating Procedure (SOP) for trade receivables collection at PT ABC, a company in the food and beverage (FnB) sector.The SOP is designed to provide structured guidance in the collection process, starting from identifying overdue receivables, sending reminders through official letters, to ensuring timely payment settlement. The SOP development was carried out through observations, interviews, and data analysis to ensure its alignment with the company's operational needs. It is expected that the implementation of this SOP will minimize the risk of problematic receivables, support smooth operations, and maintain the company's cash flow stability in a sustainable manner.